2019
DOI: 10.3390/metabo9050104
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease, and the Underlying Altered Fatty Acid Metabolism, Reveals Brain Hypoperfusion and Contributes to the Cognitive Decline in APP/PS1 Mice

Abstract: Non-alcoholic fatty liver disease (NAFLD), the leading cause of chronic liver disease, is associated with cognitive decline in middle-aged adults, but the mechanisms underlying this association are not clear. We hypothesized that NAFLD would unveil the appearance of brain hypoperfusion in association with altered plasma and brain lipid metabolism. To test our hypothesis, amyloid precursor protein/presenilin-1 (APP/PS1) transgenic mice were fed a standard diet or a high-fat, cholesterol and cholate diet, induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 85 publications
2
27
0
Order By: Relevance
“…Their findings suggested an acceleration in neurodegeneration and in Aβ plaque formation after HFD-induced acute inflammation and NAFLD development [30]. The fact that HFD and fructose-rich diets may quicken AD cognitive decline has also been confirmed in recent experimental studies [32][33][34].…”
Section: Neurodegenerative Diseases: Alzheimer's Diseasementioning
confidence: 83%
“…Their findings suggested an acceleration in neurodegeneration and in Aβ plaque formation after HFD-induced acute inflammation and NAFLD development [30]. The fact that HFD and fructose-rich diets may quicken AD cognitive decline has also been confirmed in recent experimental studies [32][33][34].…”
Section: Neurodegenerative Diseases: Alzheimer's Diseasementioning
confidence: 83%
“…Changes in rCBF occur earlier than rCBV during the disease course [98], where metabolic and vascular risk factors have been implicated as a driver of hemodynamic disturbances [102,103]. Consistent, experimental studies have shown that these risk factors compromises cerebral perfusion, contribute to cognitive impairment and enhances AD pathology [104,105]. The variability of hemodynamic read-outs in AD and the fact that hemodynamic changes are also common in other forms of dementia limits the utility of methods for the individual diagnosis of AD patients, but the methods remain pivotal research tools.…”
Section: Dysregulation Regional Rcbf and Volumementioning
confidence: 99%
“…Oxidative phosphorylation and metabolic pathways appear disrupted at this early stage and have been associated with early stages of human AD [23,24]. In addition, non-alcoholic liver fatty liver disease (NAFLD) was also identified at this early stage and has been previously associated with AD [25,26]. NAFLD is generally characterized by excessive fat build up in the liver.…”
Section: Discussionmentioning
confidence: 99%